The student teams achievement divisions (STAD) learning model and the role of digital media in the opinion-forming ability of students at SMAN 1 Negerikaton - Dwi Ratna Sari; Susanto Susanto; Widiyanto Widiyanto (International Journal of Science and Applied Science: Conference Series, 2025)
Education today requires students to not only be proficient in academic knowledge, but also to have the ability to think critically and dare to express their opinions clearly, logically, systematically, rationally, and responsibly. Unfortunately, in learning practices, many students are still passive and less involved in classroom discussions. The ability to express opinions is an important aspect that can reflect the character of students who are active, confident, and communicative. This article presents the results of research on the influence of the Student Teams Achievement Divisions (STAD) learning model and the use of digital media (Quizizz) on improving students' ability to express their opinions. The study was conducted at SMAN 1 Negerikaton, involving 141 tenth-grade students out of a total population of 216 students, selected using the Proportionate Stratified Random Sampling technique. The instrument used was a closed-ended Likert scale questionnaire, and the data was analyzed using multiple linear regression. The results of this study indicate that the STAD model has a significant effect of 68.2%, and digital media such as Quizizz has an effect of 56.6% on students' opinion-forming abilities. Together, these two approaches contributed 73.9% to increasing student participation in expressing opinions. The combination of cooperative learning strategies and digital media not only encourages students to speak more actively but also increases social interaction, conceptual understanding, and student confidence. This proves that collaboratively designed technology-based learning can be an effective solution to overcome one-way and boring learning. Therefore, teachers and education practitioners are advised to make optimal use of this strategy in an effort to develop students who are critical thinkers, communicative, and ready to face the challenges of the 21st century.